'See These Brilliant Exponents of the Game': The England Women's Hockey Team Tour of Australia and New Zealand, 1914. Issue 17 (21st November 2016) - Watson, Geoff
Abstract: This paper argues that the 1914 England Women's hockey tour of Australia and New Zealand has an ambiguous place within wider progress narratives of women's sport. It created some important sporting precedents, being the first time Australian and New Zealand women's teams had taken the field. The media reception of the tour was mixed. While the social pages and some of match commentary focused on the appearance of the players, the majority presented the tour as a worthy sporting spectacle. Indeed in the final match the New Zealand team was billed as the 'All Blacks', the name normally associated with national men's teams. Moreover, the symbolic importance of the tour was enhanced by the fact that the tourists were accorded the same rites and rituals accorded men's touring teams to New Zealand: parliamentary and civic receptions; playing in the leading sporting venues and being linked to imperial bonding.